A comprehensive methodological workflow to maximize solar energy in low-voltage grids: A case study of vertical bifacial panels in Nordic conditions - Jouttijärvi S; Thorning J; Manni M; Huerta H; Ranta S; Di Sabatino M; Lobaccaro G; Miettunen K (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
The large-scale deployment of solar photovoltaic (PV) panels in residential and commercial buildings affects the local distribution grid. Voltage rises during times when PV production exceeds consumption can limit the hosting capacity of the distribution grid. This study presents a comprehensive methodological workflow that moves from the solar analysis of an ideal district to the identification of the PV hosting capacity of a distribution grid. The workflow aims to be highly flexible: the input parameters (i.e., PV technology, PV orientation, global horizontal solar irradiation, and grid properties) can be varied to simulate different cases and compare the corresponding hosting capacities. This workflow enables the analysis of the influences of PV systems' properties and orientation, electricity consumption, and grid characteristics on a grid's hosting capacity. A case study was conducted in which the IEEE European Low Voltage Test Grid was used, and conventionally mounted monofacial photovoltaic (MPV) panels were progressively replaced with east-west oriented, vertically mounted bifacial photovoltaic (VBPV) panels that can provide a better match with the electricity load and a higher daily total to daily peak electricity production ratio. The benefits of VBPV are highlighted at high-latitude locations, such as Nordic countries. Therefore, Turku, Finland, which is at a representative Nordic latitude considering the locations of the most important population centers, was chosen as the location for the case study. The results showed that applying VBPV increased a grid's PV hosting capacity significantly, up to 46% with the optimal system (30% MPV and 70% VBPV).